An Experimental Study on the Way Bottom Widening of Pier Foundations Affects Seismic Resistance - Nagao, T. (Engineering, Technology & Applied Science Research, 2020)
The resistance of a pier to horizontal loads, like seismic loads, is due to the flexural rigidity of its foundations and the horizontal subgrade reaction. In the event of a massive earthquake, the latter becomes very small because of the softening of the ground, while the structure may experience a large inertial force and lateral spreading pressure. Therefore, structures with high seismic resistance are required in areas with high seismicity. When a wide caisson is used as a pier foundation, a rotational resistance moment caused by the vertical subgrade reaction acting on the foundation bottom can be expected. Although this rotational resistance moment increases if the foundation is widened, in design practice the subgrade reaction coefficient is evaluated as being low under such circumstances. Therefore, even if the foundation is widened, the rotational resistance moment does not increase greatly. Rotational resistance commensurate with the increased construction cost due to foundation widening cannot be expected. In the present study, horizontal loading experiments were performed at one pier with a normal foundation and at one with widened at the bottom foundation, and the way that the widening affected the seismic performance was examined. The results show that compared with the normal foundation, the bottom-widened one experienced far less displacement and offered higher earthquake resistance.